Public provision of employment support services to youth jobseekers: Effects on informality and wages in transition economies. Issue 6 (3rd September 2018) - Petreski, Marjan
Abstract : Purpose: The purpose of this paper is to investigate if public provision of employment support services to youth leads to reduced informality and increased wages in transition economies. Design/methodology/approach: The author uses the school-to-work transition data sets of the International Labor Organization for seven transition economies of Southeast Europe and the Commonwealth of Independent States. The author focuses on two econometric issues: the selectivity into informal employment and the endogeneity of the public employment support service provision with respect to informal employment and wages. The authors achieves identification by employing internal regressors which are uncorrelated with the product of heteroskedastic errors, a-la Lewbel (2012), as the author could not prove the external validity of the commonly used external instruments in similar contexts. Findings: Results suggest that the public provision of employment support services matters for relegating informal employment, but not for wages, in general. Placement in education or training programs is most powerful in reducing informal employment among the four different employment support services, while only advice for job search works positively for wages probably through enabling better match. Social implications: Increasing budget allocations, varying the array of public employment support measures, enhanced targeting, and advancement of the profiling system may significantly contribute to strengthening the public employment support service effect on youth employment in transition economies. Originality/value: The paper brings a couple of novelties to the current literature. First, it is among the early papers dealing with the issue of informality, public employment support service and labor market prospects of youth in general in a rigorous manner. Second, it fills an important gap for transition economies which were less researched due to the long-lasting transition process as well due to data scarcity. Third, it utilizes the recently collected School-to-Work Transition Surveys (SWTS). Finally, and likely most importantly, it thoroughly addresses the issues of selectivity bias and endogeneity of PESS by utilizing a recent approach of Lewbel (2012) whereby internally generated variables are used as instruments. Hence, the paper accounts for the endogeneity stemming from unobservables in a novel manner, contrary to the common approaches in the literature based either on propensity score matching addressing selectivity on observables only, or relying on commonly used instruments in the labor market literature – mainly regional employment variables – whose external validity is easily disputed.